2023
DOI: 10.2478/sjph-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcomes during the COVID-19 epidemic in pregnancies complicated by gestational diabetes

Abstract: Introduction Gestational diabetes (GDM) is one of the most common complications in pregnancy, with a prevalence that continues to rise. At the time of the COVID-19 epidemic, immediate reorganisation and adjustment of the system was needed. Telemedicine support was offered in order to provide high-quality treatment to pregnant women. However, the success of the treatment is unknown. We therefore aimed to evaluate COVID-19 epidemic effects on pregnancy outcomes in GDM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…An infection by itself may not be a risk factor unless it occurs very early in pregnancy. The association between severe COVID-19 and LGA (1.53) is similar to the results reported by Munda et al (1.24) and Simon et al (1.38), though their associations were smaller in magnitude and not statistically significant 57 64. A higher proportion of macrosomia (12%) was reported among women who had pregnancies during lockdown, compared with pregnancies (9%) at the same time the preceding year 65.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…An infection by itself may not be a risk factor unless it occurs very early in pregnancy. The association between severe COVID-19 and LGA (1.53) is similar to the results reported by Munda et al (1.24) and Simon et al (1.38), though their associations were smaller in magnitude and not statistically significant 57 64. A higher proportion of macrosomia (12%) was reported among women who had pregnancies during lockdown, compared with pregnancies (9%) at the same time the preceding year 65.…”
Section: Discussionsupporting
confidence: 86%
“…Lack of exercise and an increase in sedentary behaviour during the pandemic could have led to excess gestational weight gain without leading to clinical disease. Excess weight gain during pregnancy and increase in gestational diabetes, both risk factors for severe COVID-19 and LGA,56 have been observed during the pandemic among Hispanics 57 58. Further, COVID-19 early in pregnancy may have increased the risk of fetal death due to heightened antibody reaction leading to rejection of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes protocols were altered n Australia [38], Canada [39], and the UK [16] switching to virtual monitoring and/or relying on solely fasting glucose concentrations for diagnosis. Few countries, including Slovenia and Italy, maintained traditional gestational diabetes screening protocols [46]. Many institutions in the UK, France, Italy, New Zealand, the Netherlands, Spain, Canada, and Australia implemented measures to decreased viral spread during in-person appointments including social distancing, equipment sanitization, limiting support persons during visits, and increased personal protective equipment [12, 16, 19, 23, 28, 29, 31-33, 40, 41].…”
Section: Plos Onementioning
confidence: 99%
“…There were mixed results on the impact of COVID-19 on induction of labour [IOL], including the mode of delivery and location of birth. Three studies found no or little change to the number of inductions performed [24,45,46]. However, in the UK, 23% of Trusts and Boards switched to mechanical induction exclusively as it was perceived as safer for home use [45].…”
Section: Intrapartum Carementioning
confidence: 99%
“…The utilization of telehealth services displayed several advantages, including mitigating the risk of COVID-19 exposure, enhancing healthcare accessibility, and reducing expenses associated with travel and parking[ 73 ]. A study conducted by Munda et al [ 74 ] further revealed that transitioning clinic visits to telehealth did not compromise glycemic control or lead to adverse neonatal outcomes. This highlights the efficacy of telehealth in providing obstetric care.…”
Section: Clinical Challengesmentioning
confidence: 99%